Operationalising the capability approach: developing culturally relevant indicators of indigenous wellbeing – an Australian example. (2nd July 2016) - Yap, Mandy; Yu, Eunice
Abstract: The tension that exists between the worldviews of Indigenous peoples and government reporting frameworks is what Taylor has termed 'the recognition or translation space'. The meaningful operation of the 'recognition space' hinges on four key points – firstly, why measure wellbeing, secondly, how wellbeing is conceptualised, thirdly, by what process the wellbeing measures are decided, and finally, who makes those decisions. Sen's capability approach is concerned with development as a process of expanding people's freedoms to live the life they have reason to value. It is in this spirit of freedom that Sen has not prescribed a fixed list of functioning and capabilities. The open-ended nature of this approach, in letting the identification of important capabilities be dependent on specific contexts and people's own values, aligns with the United Nations Declaration on the Rights of Indigenous peoples which asserts that Indigenous people must be agents of their own development. This paper contributes to the understanding of what a good life means by augmenting the capability approach to incorporate Indigenous worldviews. Through participatory research methodologies we define and select indicators of wellbeing which are grounded in the lived experiences of the Yawuru people in Broome, Western Australia.